Renal Failure in Pregnancy: Case Reports and Review of the Literature - Yetkin Karasu; Berna Dilbaz; Kahraman Ülker (Gynecology Obstetrics & Reproductive Medicine)
Acute renal failure (ARF) is rarely associated with pregnancy. However, it is a severe health-deteriorating problem of pregnant women without a known kidney disease. Although its incidence is relatively low in developed countries (1/20000), it is still a serious health issue in the developing world. In addition to any of the etiological factors that may result in ARF in non-pregnant women, pregnancy also increases the vulnerability of some special diseases that may result with the renal injury. In this review we aimed to summarize antepartum and postpartum causes of renal failure via summarizing two cases of renal failure.